Ewolucja środków zabezpieczających w polskim prawie karnym - Niewiadomska-Krawczyk, Magdalena (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The paper focuses on restraining measures regarded as one of a group of measures of society’s response to prohibited acts. Restraining measures were introduced into the Polish legal system by the 1932 Criminal Code. Since then the form of the measures has changed substantially, not only as a result of the entry into force of new criminal regulations but also as a result of amendments to criminal law, especially the one introduced by the Act of 20 February 2015 resulting in a remodelling of the system of restraining measures and rules of their application. An important task has also been to determine the meaning of the term restraining measures.
Keywords: środki zabezpieczające; polskie prawo karne; niebezpieczny sprawca